2009
DOI: 10.1007/s00415-009-5338-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain volume analyses and somatosensory evoked potentials in multiple system atrophy

Abstract: We investigated a progression of brain atrophy and somatosensory system dysfunction in multiple system atrophy (MSA). Subjects were 21 MSA patients [12 MSA-C (cerebellar type) and 9 MSA-P (parkinsonism type)]. The relative volumes of cerebrum, brainstem and cerebellum to the intracranial volume were obtained from three-dimensional computed tomography (3D-CT) of the brain. The median nerve somatosensory evoked potentials (SEPs) were recorded, and the latencies and amplitudes of N9, N11, P13/14, N20 and P25 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…A previous SEP study reported that the central sensory conduction time was progressively prolonged in parallel with disease duration in MSA [39]. In this study, since the peak N20 latencies were not prolonged in either PD or MSA-P, the timing of TMS over the M1 appears to be appropriate for inducing cortical plasticity in the M1.…”
Section: Discussionsupporting
confidence: 49%
“…A previous SEP study reported that the central sensory conduction time was progressively prolonged in parallel with disease duration in MSA [39]. In this study, since the peak N20 latencies were not prolonged in either PD or MSA-P, the timing of TMS over the M1 appears to be appropriate for inducing cortical plasticity in the M1.…”
Section: Discussionsupporting
confidence: 49%
“…For this reason, the usefulness of brain CT in MSA is limited, and should only be used in patients with contraindications to magnetic resonance (MR) imaging (i.e., pacemaker, metal implants). Brain volumetric analysis obtained from 3-dimensional CT scans, however, could be useful to monitor disease progression in MSA (Miyatake et al, 2010). …”
Section: Brain and Cardiac Neuroimagingmentioning
confidence: 99%
“…In patients with MSA-C, for example, structural imaging data indicate that cerebellar volume is reduced in even early stages of MSA (Dash et al, 2018), and the related gray matter (GM) loss bears a significant association with cognitive profiles (Kim et al, 2015). Based on a three-dimensional gyrification index, Miyatake et al (Miyatake et al, 2010) have further demonstrated that patients with the MSA-C variant show GM losses primarily in upper lobules and anterior lobes of cerebellum, determining a negative correlation between hemispheric volume and cerebellar ataxia scores. Cerebellar abnormalities are also common in the MSA-P variant, which is typically considered a basal ganglia disorder.…”
Section: Introductionmentioning
confidence: 99%